Decoding individual differences in STEM learning from functional MRI data - Joshua S. Cetron (Nature Portfolio, 2019)
People differ in their current levels of understanding of many complex concepts. Here, the authors show using fMRI that brain activity during a task that requires concept knowledge can be used to compute a ‘neural score’ of the participant’s understanding.